INFLAMMATION ROLE AND ANTI-INFLAMMATORY STRATEGIES IN ACUTE CARDIOVASCULAR PATHOLOGY - I. I. Chukaeva; N. V. Orlova; F. A. Evdokimov; V. A. Aleshkin; O. O. Soloshenkova; L. I. Novikova; N. P. Rechnova (Российский кардиологический журнал)
In patients with myocardial infarction, the dynamics of acute phase proteins (APP), oxidative stress and white blood cell functional activity was investigated. A statistically significant increase in APP levels was observed starting from Day 1, reached its peak at Day 7, and disappeared by Day 28. Acute phase parameters correlated with oxidative stress characteristics. APP levels were higher in patients with more severe clinical course. The rate of haptoglobin concentration reduction was higher in participants receiving ACE inhibitors, comparing to the control group. Therefore, ACE inhibitor therapy might affect inflammation and sclerosis processes in the infarction area.